A soft ferrite wave absorbing material and a preparation method thereof, and a composite wave absorbing material

通过掺杂非磁性金属离子调节软磁铁氧体的电磁参数,解决了铁氧体吸波材料在高频段吸收性能不足的问题,制备出具有高饱和磁化强度和广谱吸波性能的Ba1.5Sr1 .5Co2-yCuyMnxZrxFe24-2xO41 wave absorbing material, suitable for electromagnetic wave absorption of 5G communication equipment.

CN115084870BActive Publication Date: 2025-01-07XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210924419.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2025-01-07
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

In the application of high-frequency bands, existing ferrite wave absorbing materials have problems such as narrow absorption bands and weak absorption strength, and traditional preparation technology is difficult to meet the demand for electromagnetic wave absorption by 5G communication equipment.

Method used

By doping non-magnetic metal ions such as Cu2+, Mn2+ and Zr4+, the electromagnetic parameters and magnetic crystal anisotropy field of soft magnetite are adjusted, the magnetic ion coupling effect is reduced, and the saturation magnetization and absorption performance of the material are improved, and the saturation magnetization and wave absorption performance of the material are prepared. Ba1.5Sr1.5Co2-yCuyMnxZrxFe24-2xO41 soft ferrite wave absorbing material.

Benefits of technology

It significantly improves the saturation magnetization and absorption performance of the material, and realizes effective attenuation of high-frequency and very high-frequency signals. The maximum absorption frequency reaches 14.6GHz, and the bandwidth with a reflection loss value below -10dB is 10.8GHz, which is suitable for Electromagnetic wave absorption in 5G communication equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084870B_ABST
    Figure CN115084870B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electromagnetic wave absorbing materials, and provides a soft ferrite absorbing material and a preparation method thereof, as well as a composite absorbing material. The present invention weakens the coupling effect between magnetic ions by doping with non-magnetic metal ions, reduces the coercive force of the material, greatly improves the saturation magnetization, and has a good attenuation effect on high-frequency and very high-frequency signals; and adjusts the electromagnetic parameters and magnetocrystalline anisotropy field and other properties of the material by appropriate element doping, greatly improving the absorbing performance and effective absorption bandwidth. The results of the embodiment show that the saturation magnetization of the absorbing material is as high as 78.79emu / g, the minimum reflection loss is ‑51dB, the maximum absorbing frequency is 14.6GHz, and the maximum bandwidth with a reflection loss value lower than ‑10dB (>90% electromagnetic wave absorption rate) is 10.8GHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a soft ferrite absorbing material and a preparation method thereof, and a composite absorbing material. Background Art

[0002] With the rapid development of wireless, electromagnetic wave and microwave communication technologies, ultra-high frequency band electronic devices are becoming increasingly important in commercial applications. At present, with the improvement of mobile phone technology and intelligent development, 5G communication network will become the mainstream in the future. Compared with 3G and 4G, the frequency band of 5G is extended from centimeter band to millimeter band, which requires faster data transmission speed, higher frequency band and larger bandwidth. However, the electromagnetic radiation generated by the extensive use of high-frequency band electronic devices has caused great harm to human health. It may heat human cells or interfere with the inherent electromagnetic field of the human body, thereby having an adverse effect on human health, and high-intensity electromagnetic radiation may interfere with the normal operation of digital devices, thereby affecting the quality of communication. Therefore, the development of various new electromagnetic wave absorption materials and the effective elimination or attenuation of electromagnetic radiation and electromagnetic interference have become key technologies that need to be urgently solved by current 5G communication electronic devices.

[0003] At present, the commonly used absorbing materials mainly include metal magnetic materials, ferrites, conductive carbon materials, conductive polymer materials, etc. They can absorb or attenuate electromagnetic wave energy through dielectric loss, magnetic loss and resistance loss, and convert electromagnetic energy into heat energy. Ferrite, as the most widely used absorbing material, has high magnetic permeability, high resistivity and good matching impedance performance. However, traditional spinel ferrites such as Ni-Zn and Mn-Zn ferrites are not conducive to their application in the GHz frequency band due to the Snoek formula, and the ferrite absorbing materials prepared by the existing preparation technology still have problems such as narrow absorption band and weak absorption intensity.

[0004] Therefore, developing a new type of adjustable soft ferrite absorbing material and improving the electromagnetic impedance matching by adjusting its electromagnetic parameters and magnetocrystalline anisotropy field and other properties, thereby improving the microwave absorption performance of the material has broad application prospects and great application value. Summary of the invention

[0005] In view of this, the present invention provides a soft ferrite absorbing material and a preparation method thereof, as well as a composite absorbing material. The present invention reduces the coupling effect between magnetic ions by doping with non-magnetic metal ions, reduces the coercive force of the soft ferrite absorbing material, greatly improves its saturation magnetization, has a good attenuation effect on high-frequency and very high-frequency signals, and adjusts the electromagnetic parameters and magnetocrystalline anisotropy field of the material by appropriate element doping, greatly improving the absorbing performance and effective absorption bandwidth.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A soft ferrite absorbing material, the chemical formula is: Ba 1.5 Sr 1.5 Co 2-y Cu y Mn x Zr x Fe 24-2x O 41 , where the value range of y is 0<y≤1.0, and the value range of x is 0<x≤1.0.

[0008] The present invention also provides a method for preparing the soft magnetic ferrite absorbing material described in the above scheme, comprising the following steps:

[0009] Mixing barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions, iron ions and deionized water according to a stoichiometric ratio to obtain a metal ion mixed solution;

[0010] The metal ion mixed solution and alkaline solution are mixed to perform precipitation reaction to obtain a precursor;

[0011] The precursor is calcined to obtain the soft magnetic ferrite wave absorbing material.

[0012] Preferably, the barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions and iron ions are derived from water-soluble salts corresponding to the respective ions.

[0013] Preferably, the water-soluble salts corresponding to the barium ions, strontium ions, cobalt ions, copper ions and zirconium ions are nitrates or chlorides; and the water-soluble salts corresponding to the manganese ions are nitrates, acetates or chlorides.

[0014] Preferably, the alkali solution is a mixed solution of sodium carbonate and sodium hydroxide; the total concentration of sodium carbonate and sodium hydroxide in the mixed solution is 1.0 to 2.5 mol·L -1 ; The molar ratio of the total amount of metal ions in the metal ion mixed solution to the sodium carbonate and sodium hydroxide in the alkali solution is 1-3:2-4:0.5-2; the temperature of the precipitation reaction is 50-100°C and the time is 1-5h.

[0015] Preferably, the calcination temperature is 1050-1450° C. and the calcination time is 2-10 hours.

[0016] The present invention also provides a composite absorbing material, the preparation raw materials of which include epoxy resin, epoxy curing agent and soft ferrite absorbing material; the soft ferrite absorbing material is the soft ferrite absorbing material described in the above scheme or the soft ferrite absorbing material prepared by the preparation method described in the above scheme.

[0017] Preferably, the usage amount of the epoxy resin is 5-35% of the weight of the soft ferrite absorbing material, and the usage amount of the epoxy curing agent is 2-15% of the weight of the soft ferrite absorbing material.

[0018] Preferably, the epoxy resin is at least one of bisphenol A epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin, and the epoxy curing agent is at least one of phthalic anhydride curing agent, aliphatic polyamine curing agent and low molecular weight polyamide curing agent.

[0019] The present invention also provides a method for preparing the composite absorbing material described in the above scheme, comprising the following steps:

[0020] The epoxy resin, the soft magnetic ferrite absorbing material and the epoxy curing agent are mixed, pressed and baked in sequence, and cooled to obtain the composite absorbing material.

[0021] The present invention provides a soft ferrite wave absorbing material, the chemical formula of which is: Ba 1.5 Sr 1.5 Co 2-y Cu y Mn x Zr x Fe 24- 2x O 41 , wherein the value range of y is 0<y≤1.0, and the value range of x is 0<x≤1.0. 2+ Ion pair Co 2+ ions are substituted, on the one hand, Cu 2+ The melting point is low, and the appropriate Cu 2+ It helps to reduce the sintering temperature, and Co 2+ The magnetocrystalline anisotropy of ions is stronger than that of Cu 2+ Ion, Cu 2+ The substitution of ions reduces the magnetocrystalline anisotropy of ferrite, which is beneficial to reduce the coercive force H c , and non-magnetic metal ions to Fe 3+ Ion doping weakens the superexchange interaction between tetrahedral and octahedral sites, and Zr 4+ The ions preferentially occupy the 4f1 spin-down site, which reduces the spin-down magnetic moment and increases the net magnetic moment, thus greatly increasing the saturation magnetization. According to the superexchange interaction theory, Mn 2+ Ions as multivalent ions Fe 3+The local bonding distortion caused by ion doping leads to an increase in exchange energy, and the distortion increases the magnetocrystalline anisotropy, thereby affecting the frequency-dependent complex magnetic permeability and complex dielectric constant, greatly improving the material's absorbing performance and effective absorption bandwidth. The results of the embodiment show that the saturation magnetization intensity of the soft ferrite absorbing material provided by the present invention is as high as 78.79emu / g, the minimum reflection loss is -51dB, the maximum absorbing frequency is 14.6GHz, and the maximum bandwidth with a reflection loss value lower than -10dB (>90% electromagnetic wave absorption rate) is 10.8GHz.

[0022] The present invention also provides a method for preparing the soft ferrite described in the above scheme. The preparation method provided by the present invention has simple steps and is easy to operate.

[0023] The present invention also provides a composite wave-absorbing material, which is obtained by compounding the soft ferrite described in the above scheme with epoxy resin. The composite wave-absorbing material has good wave-absorbing performance and low reflection loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the soft ferrite absorbing material obtained in Example 1 of the present invention;

[0025] Figure 2 The magnetic performance diagram of the soft ferrite absorbing materials obtained in Examples 1 to 5 of the present invention and the absorbing materials obtained in Comparative Examples 1 to 3;

[0026] Figure 3 This is a magnetic performance diagram of the soft ferrite absorbing material obtained in Example 3 of the present invention;

[0027] Figure 4 The diagram is a wave absorbing performance diagram of the soft ferrite composite wave absorbing materials obtained in Examples 2 to 5 of the present invention and the wave absorbing materials in Comparative Examples 1 to 2 in the 2 to 18 GHz frequency band;

[0028] Figure 5 This is a curve diagram of the absorbing performance of the soft ferrite composite absorbing material with different coating thicknesses obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The present invention provides a soft ferrite wave absorbing material, the chemical formula of which is: Ba 1.5 Sr 1.5 Co 2-y Cu y Mn x Zr x Fe 24- 2x O 41 , where the value range of y is 0<y≤1.0, and the value range of x is 0<x≤1.0.

[0030] In the present invention, the value range of y is preferably 0.05 to 0.85, specifically 0.05, 0.65 or 0.85, and the value range of x is preferably 0.15 to 0.95, specifically 0.15, 0.35 or 0.95.

[0031] The present invention also provides a method for preparing the soft magnetic ferrite absorbing material described in the above scheme, comprising the following steps:

[0032] Mixing barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions, iron ions and deionized water according to a stoichiometric ratio to obtain a metal ion mixed solution;

[0033] The metal ion mixed solution and alkaline solution are mixed to perform precipitation reaction to obtain a precursor;

[0034] The precursor is dried and calcined in sequence to obtain a soft magnetic ferrite wave absorbing material.

[0035] The present invention mixes barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions, iron ions and deionized water according to a stoichiometric ratio to obtain a metal ion mixed solution. In the present invention, the barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions and iron ions are derived from water-soluble salts corresponding to the respective ions, wherein the water-soluble salts corresponding to the barium ions, strontium ions, cobalt ions, copper ions and zirconium ions are preferably nitrates or chlorides; the water-soluble salts corresponding to the manganese ions are preferably nitrates, acetates or chlorides. In a specific embodiment of the present invention, the water-soluble salts used are specifically barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate and iron nitrate. In the present invention, in the metal ion mixed solution, the concentration of copper ions is preferably 0.001-0.02 mol / L, the concentration ratio of copper ions to cobalt ions is preferably (0.11-0.43):1, and the concentration ratio of manganese ions, zirconium ions and iron ions is preferably (0.004-0.046):(0.004-0.046):1. In a specific embodiment of the present invention, the above metal salts are preferably added to deionized water and then stirred for 30 minutes to obtain a metal ion mixed solution.

[0036] After obtaining the metal ion mixed solution, the present invention mixes the metal ion mixed solution with an alkali solution to perform a precipitation reaction to obtain a precursor. In the present invention, the alkali solution is preferably a mixed solution of sodium carbonate and sodium hydroxide; the total concentration of sodium carbonate and sodium hydroxide in the mixed solution is preferably 1.0 to 2.5 mol / L, more preferably 1.8 to 2.05 mol·L -1; The molar ratio of the total amount of metal ions in the metal ion mixed solution to the sodium carbonate and sodium hydroxide in the alkali solution is preferably 1-3:2-4:0.5-2, more preferably 1:2.8-2.9:1.1-1.2; The temperature of the precipitation reaction is preferably 50-100°C, more preferably 60-80°C, and the time is preferably 1-5h, more preferably 1-3h. In a specific embodiment of the present invention, the alkali solution is preferably added dropwise to the metal ion mixed solution under stirring, and the precipitation reaction time is counted from the completion of the dropwise addition of the alkali solution.

[0037] After the precipitation reaction is completed, the present invention preferably filters the obtained reaction solution, and then washes and dries the obtained solid product in sequence to obtain a precursor powder; the washing is preferably water washing, and the pH value is preferably 7 to 8; the drying temperature is preferably 100 to 120°C, and the time is preferably 8 to 12 hours.

[0038] After obtaining the precursor powder, the present invention calcines the precursor to obtain a soft magnetic ferrite absorbing material. In the present invention, the calcination temperature is preferably 1050-1450°C, more preferably 1100-1350°C, the calcination time is preferably 2-10 hours, more preferably 2-5 hours; the calcination is preferably carried out in a muffle furnace; after the calcination is completed, it is cooled to room temperature.

[0039] In a specific embodiment of the present invention, after calcination, the obtained soft ferrite absorbing material is preferably ground and sieved to obtain soft ferrite absorbing material powder; the grinding is preferably carried out in a mortar, and the mesh size of the sieve is preferably 200 meshes.

[0040] The present invention also provides a composite wave absorbing material, the preparation raw materials of which include epoxy resin, epoxy curing agent and soft ferrite; the soft ferrite wave absorbing material is the soft ferrite wave absorbing material described in the above scheme.

[0041] In the present invention, the usage amount of the epoxy resin is preferably 5 to 35% of the weight of the soft ferrite powder, more preferably 10 to 30%, and further preferably 15 to 25%. The usage amount of the epoxy curing agent is preferably 2 to 15% of the weight of the soft ferrite powder, more preferably 5 to 10%, and further preferably 6 to 8%.

[0042] In the present invention, the epoxy resin is preferably at least one of bisphenol A epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin, and the epoxy curing agent is preferably at least one of phthalic anhydride curing agent, aliphatic polyamine curing agent and low molecular weight polyamide curing agent; the present invention has no special requirements on the specific types of the above curing agents, and those familiar to those skilled in the art can be used.

[0043] The present invention also provides a method for preparing the composite absorbing material described in the above scheme, comprising the following steps:

[0044] The epoxy resin, the soft ferrite and the epoxy curing agent are mixed, pressed and baked in sequence, and the soft ferrite composite wave absorbing material is obtained after cooling.

[0045] In a specific embodiment of the present invention, it is preferred to first stir the epoxy resin and the soft ferrite uniformly, then add the curing agent, continue stirring for 0.5h, and then perform compression molding. In the present invention, the compression molding pressure is preferably 1.3 to 2.1 tons. In a specific embodiment of the present invention, it is preferred to first pre-press at a pressure of 1.3 to 1.8 tons for 10 to 30 seconds, and then press at a pressure of 1.6 to 2.1 tons for 30 to 60 seconds. In the present invention, the baking temperature is preferably 150°C, and the time is preferably 20 minutes.

[0046] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0047] Example 1

[0048] Ba 1.5 Sr 1.5 Co 1.15 Cu 0.85 Mn 0.15 Zr 0.15 Fe 23.7 O 41 Preparation of soft ferrite absorbing materials:

[0049] (1) Barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:0.76:0.56:0.1:0.1:15.8, and deionized water is added and stirred to obtain a metal salt solution.

[0050] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.9:1.1, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0051] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0052] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0053] (5) The solid prepared in step (4) is fully ground and sieved in a mortar to obtain a brown powder, which is a high saturation magnetization soft ferrite absorbing material.

[0054] Example 2

[0055] Ba 1.5 Sr 1.5 Co 1.35 Cu 0.65 Mn 0.35 Zr 0.35 Fe 23.3 O 41 Preparation of soft ferrite absorbing materials:

[0056] (1) Barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:0.9:0.43:0.23:0.23:15.53, and deionized water is added and stirred to obtain a metal salt solution.

[0057] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.9:1.1, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0058] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0059] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0060] (5) The solid obtained in step (4) is fully ground and sieved in a mortar to obtain a brown powder, which is a high saturation magnetization soft ferrite absorbing material.

[0061] Example 3

[0062] Ba 1.5 Sr 1.5 Co 1.55 Cu 0.45 Mn 0.55 Zr 0.55 Fe 22.9 O 41 Preparation of soft ferrite absorbing materials:

[0063] (1) Barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:1.03:0.3:0.37:0.37:15.26, and deionized water is added and stirred to obtain a metal salt solution.

[0064] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0065] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0066] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0067] (5) The solid obtained in step (4) is fully ground and sieved in a mortar to obtain a brown powder, which is a high saturation magnetization soft ferrite absorbing material.

[0068] Example 4

[0069] Ba 1.5 Sr 1.5 Co 1.75 Cu 0.25 Mn 0.75 Zr 0.75 Fe 22.5 O 41 Preparation of soft ferrite absorbing materials:

[0070] (1) Barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:1.16:0.17:0.5:0.5:15, and deionized water is added and stirred to obtain a metal salt solution.

[0071] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0072] (3) Filtering, washing and drying: the precursor solution of step (2) is filtered, washed repeatedly with deionized water until the pH value reaches 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0073] (4) Calcination: The precursor powder prepared in step (3) is placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0074] (5) The solid obtained in step (4) is fully ground and sieved in a mortar to obtain a brown powder, which is a high saturation magnetization soft ferrite absorbing material.

[0075] Example 5

[0076] Ba 1.5 Sr 1.5 Co 1.95 Cu 0.05 Mn 0.95 Zr 0.95 Fe 22.1 O 41 Preparation of soft ferrite absorbing materials:

[0077] (1) Barium nitrate, strontium nitrate, cobalt nitrate, copper chloride, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:1.3:0.03:0.63:0.63:14.73, and deionized water is added and stirred to obtain a metal salt solution.

[0078] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0079] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0080] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0081] (5) The solid obtained in step (4) is fully ground and sieved in a mortar to obtain a brown powder, which is a high saturation magnetization soft ferrite absorbing material.

[0082] Comparative Example 1

[0083] Ba 1.5 Sr 1.5 Co 1.35Cu 0.65 Fe 24 O 41 Preparation of soft ferrite absorbing materials:

[0084] (1) Barium nitrate, strontium nitrate, cobalt nitrate, cupric chloride, and ferric nitrate are mixed in a molar ratio of 1:1:0.9:0.43:16, and deionized water is added and stirred to obtain a metal salt solution.

[0085] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0086] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0087] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0088] (5) The solid obtained in step (4) is fully ground in a mortar and sieved to obtain a brown powder which is a soft magnetic ferrite absorbing material.

[0089] Comparative Example 2

[0090] Ba 1.5 Sr 1.5 Co2Mn 0.65 Zr 0.65 Fe 22.7 O 41 Preparation of soft ferrite absorbing materials:

[0091] (1) Barium nitrate, strontium nitrate, cobalt nitrate, manganese chloride, zirconium nitrate, and iron nitrate are mixed in a molar ratio of 1:1:1.33:0.43:0.43:15.13, and deionized water is added and stirred to obtain a metal salt solution.

[0092] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0093] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0094] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0095] (5) The solid obtained in step (4) is fully ground in a mortar and sieved to obtain a brown powder which is a soft magnetic ferrite absorbing material.

[0096] Comparative Example 3

[0097] Ba 1.5 Sr 1.5 Co2Fe 24 O 41 Preparation of soft ferrite absorbing materials:

[0098] (1) Barium nitrate, strontium nitrate, cobalt nitrate, and iron nitrate are mixed in a molar ratio of 1:1:1.33:16, and deionized water is added and stirred to obtain a metal salt solution.

[0099] (2) Add 1.85 mol·L of the metal salt solution in step (1) dropwise -1 A mixed solution of NaOH and Na2CO3, wherein the molar ratio of the total amount of metal ions to sodium carbonate and sodium hydroxide is 1:2.8:1.2, is fully stirred to allow it to completely precipitate to obtain a precursor solution.

[0100] (3) The precursor solution of step (2) was filtered, washed repeatedly with deionized water until the pH value reached 7 to 8, and dried in an oven at 100° C. for 8 h to obtain a precursor powder.

[0101] (4) The precursor powder prepared in step (3) was placed in a muffle furnace and calcined at 1120° C. for 2 h, and then cooled to room temperature.

[0102] (5) The solid obtained in step (4) is fully ground in a mortar and sieved to obtain a brown powder which is a soft magnetic ferrite absorbing material.

[0103] Performance Test:

[0104] 1. Morphology test

[0105] Figure 1 This is a scanning electron microscope image of the soft ferrite absorbing material prepared in Example 1. Figure 1 It can be seen that the soft ferrite particles obtained in Example 1 are nano-scale, with a particle size of less than 200 nm, and the nanoparticles are regular in shape and relatively uniform in size.

[0106] 2. VSM magnetic properties performance test

[0107] The magnetic properties (saturation magnetization, remanence and coercivity) of the soft ferrite absorbing materials prepared in the above examples and comparative examples were tested using a 7404-1700GS vibrating sample magnetometer (VSM). The results are shown in Tables 1 and Figure 2 .

[0108] Table 1 VSM magnetic properties test results

[0109]

[0110] According to Table 1 and Figure 2 It can be seen that compared with the absorbing materials in Comparative Examples 1 to 3, the soft ferrite absorbing material obtained in the present invention has a higher saturation magnetization intensity, which can reach up to 78.79emu / g, and has a lower remanence and coercive force, which are 1.07emu / g and 7.29Oe respectively.

[0111] Figure 3 The magnetic properties of the soft ferrite absorbing material obtained in Example 3 are shown in FIG. Compared with Examples 1 and 2, the non-magnetic metal ions in the absorbing material in Example 3 have a great influence on Fe 3+ The increase in the amount of ion doping reduces the superexchange interaction between magnetic metals, increases the net magnetic moment, and the saturation magnetization can be as high as 78.79emu / g. Compared with Examples 4 and 5, the absorbing material of Example 3 has the best ion doping ratio. The soft ferrite absorbing materials prepared by the present invention all have a high saturation magnetization, indicating that the soft ferrite absorbing materials prepared by the present invention have better magnetic properties.

[0112] 3. Reflection loss test

[0113] The soft ferrite absorbing materials prepared in the above examples and comparative examples were mixed with epoxy resin to prepare composite absorbing materials, wherein the amount of epoxy resin used was 25% of the mass of the soft ferrite absorbing material, and after stirring evenly, 7% of epoxy curing agent was added, and stirring was continued for 0.5 hours, and the materials were pressed into coaxial rings with an outer diameter of 7 mm, an inner diameter of 3.04 mm, and a thickness of 2 mm, and then baked and cooled to room temperature. The complex dielectric constant and complex magnetic permeability of the samples were tested using an Agilent N5222A vector network analyzer, and finally the reflection loss of the material to electromagnetic waves was calculated using the transmission line theory.

[0114] Figure 4 The following is a graph showing the wave absorption performance of the soft ferrite composite wave absorbing materials obtained in Examples 2 to 5 and the wave absorbing materials in Comparative Examples 1 to 2 in the 2 to 18 GHz frequency band when the coating thickness is 2 mm (i.e., the thickness of the circular ring). Figure 4It can be seen that compared with the absorbing materials in Comparative Examples 1 to 2, the triple ion co-doping absorbing performance used in the present invention is far superior to single ion doping and double ion doping, with a minimum reflection loss of -51 dB, a maximum absorbing frequency of 14.6 GHz, and a maximum bandwidth of 10.8 GHz with a reflection loss value below -10 dB.

[0115] According to the above method, the soft ferrite and epoxy resin prepared in Example 3 were prepared into rings of different thicknesses (1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm), and the wave absorbing performance was tested. The results are as follows: Figure 5 shown. Figure 5 The following is a graph showing the wave absorption performance of the soft ferrite composite wave absorbing material obtained in Example 3 of the present invention at different coating thicknesses. Figure 5 It can be seen that when the coating thickness is 2 mm, it exhibits the highest absorption value, the reflection loss is -48.3 dB, and the absorption bandwidth is 6.2 GHz.

[0116] The above-mentioned examples show that the present invention prepares a nano-scale soft ferrite absorbing material with high saturation magnetization intensity by co-substituting three ions of Cu-Mn-Zr. 2+ Ion pair Co 2+ ions are substituted, due to Co 2+ The magnetocrystalline anisotropy of ions is stronger than that of Cu 2+ Ion, Cu 2+ The substitution of ions reduces the magnetocrystalline anisotropy of ferrite, thereby reducing the coercive force Hc, while the non-magnetic metal ions have a great influence on the magnetocrystalline anisotropy of ferrite. 3+ Ion doping weakens the superexchange interaction between tetrahedral and octahedral sites, which reduces the spin-down magnetic moment and increases the net magnetic moment, thereby greatly increasing the saturation magnetization intensity, up to 78.79emu / g. According to the superexchange interaction theory, Mn 2+ Ions as multivalent ions Fe 3 + The local bonding distortion caused by ion doping leads to an increase in exchange energy. The distortion increases the magnetocrystalline anisotropy, thereby affecting the frequency-dependent complex magnetic permeability and complex dielectric constant, greatly improving the material's absorption performance and effective absorption bandwidth. The minimum reflection loss is -51dB, the maximum absorption frequency is 14.6GHz, and the maximum bandwidth with a reflection loss value below -10dB is 10.8GHz.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A soft ferrite absorbing material, characterized in that: Chemical formula: Ba 1.5 Sr 1.5 Co 2-y Cu y Mn x Zr x Fe 24-2x O 41 , where the value range of y is 0<y≤1.0, and the value range of x is 0<x≤1.0; The preparation method of the soft magnetic ferrite absorbing material comprises the following steps: Mixing barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions, iron ions and deionized water according to a stoichiometric ratio to obtain a metal ion mixed solution; The metal ion mixed solution and alkaline solution are mixed to perform precipitation reaction to obtain a precursor; calcining the precursor to obtain the soft magnetic ferrite absorbing material; The alkali solution is a mixed solution of sodium carbonate and sodium hydroxide; the total concentration of sodium carbonate and sodium hydroxide in the mixed solution is 1.0-2.5 mol·L -1 ; The molar ratio of the total amount of metal ions in the metal ion mixed solution to the sodium carbonate and sodium hydroxide in the alkali solution is 1~3:2~4:0.5~2; the temperature of the precipitation reaction is 50~100°C and the time is 1~5 h; the temperature of the calcination is 1050~1450°C and the time is 2~10 h.

2. The method for preparing the soft ferrite absorbing material according to claim 1, characterized in that: The following steps are involved: Mixing barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions, iron ions and deionized water according to a stoichiometric ratio to obtain a metal ion mixed solution; The metal ion mixed solution and alkaline solution are mixed to perform precipitation reaction to obtain a precursor; The precursor is calcined to obtain the soft magnetic ferrite wave absorbing material.

3. The preparation method according to claim 2, characterized in that: The barium ions, strontium ions, cobalt ions, copper ions, manganese ions, zirconium ions and iron ions are derived from water-soluble salts corresponding to the respective ions.

4. The preparation method according to claim 3, characterized in that: The water-soluble salts corresponding to the barium ions, strontium ions, cobalt ions, copper ions and zirconium ions are nitrates or chlorides; the water-soluble salts corresponding to the manganese ions are nitrates, acetates or chlorides.

5. A composite absorbing material, characterized in that: The preparation raw materials include epoxy resin, epoxy curing agent and soft ferrite absorbing material; the soft ferrite absorbing material is the soft ferrite absorbing material according to claim 1 or the soft ferrite absorbing material prepared by the preparation method according to any one of claims 2 to 4.

6. The composite absorbing material according to claim 5, characterized in that: The usage amount of the epoxy resin is 5-35% of the weight of the soft ferrite absorbing material, and the usage amount of the epoxy curing agent is 2-15% of the weight of the soft ferrite absorbing material.

7. The composite absorbing material according to claim 5 or 6, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, polyphenol glycidyl ether epoxy resin, bisphenol F epoxy resin and alicyclic epoxy resin, and the epoxy curing agent is at least one of phthalic anhydride curing agent, aliphatic polyamine curing agent and low molecular weight polyamide curing agent.

8. A method for preparing the composite absorbing material according to any one of claims 5 to 7, characterized in that: The following steps are involved: The epoxy resin, the soft magnetic ferrite absorbing material and the epoxy curing agent are mixed, pressed and baked in sequence, and cooled to obtain the composite absorbing material.

Citation Information

Patent Citations

  • Layered MXene loaded cobalt ferrite composite wave-absorbing material and preparation method thereof

    CN110290691A

  • Application method of Parylene powder in iron-based soft magnetic composite material

    CN113066631A